Communication network reliability and availability estimation by the simulation method - Slavko J. Pokorni; Dušan Đ. Ostojić; Dragoljub M. Brkić (Vojnotehnički Glasnik, 2011)
The paper gives an estimation of two-terminal availability for a complex communication network (up to 50 nodes and 150 links) by a software package developed by the authors and based on the Monte Carlo simulation method and Weibull distribution. Reliability can be estimated as well. The software package is written in VISUAL BASIC 6.0 programming language on an MSI laptop with the Windows XP Professional operating system. The program execution time with over 500000 iterations is a few seconds (without graphical display). The Weibull distribution function, used for availability estimation, can be applied for electronic, electromechanical and mechanical components as well as with different failure rates.